Russian medical society on arterial hypertension (RMSAH) Consensus of Experts on the use of radiofrequency denervation of the renal arteries in patients with arterial hypertension - Nikolai M. Danilov (IP Morozov P.V., 2021)
Hyperactivity of the sympathetic nervous system is one of the basic mechanisms in the development of arterial hypertension (AH). Transcatheter renal artery denervation is aimed to destroy the renal sympathetic afferent and efferent nerves to achieve a sustained reduction in blood pressure. Since 2017, all II generation studies have demonstrated that sympathetic denervation provides clinically significant BP reduction. Russian Medical Society for Arterial Hypertension (RMSAH) experts consider SD as a possible addition to the antihypertensive strategy in patients with uncontrolled AH and recommend denervation of the renal arteries in registers and clinical trials. On the basis of existing randomized clinical trials, as well as the experience of radiofrequency denervation in Russia, the experts of RMSAH present a consensus and view of the current situation in the field of renal denervation.